Divergent Thinking: The Performance of Students with Visual Impairments on Abstract and Scenario-Based Tasks and Their Correlates. (July 2020) - Zebehazy, Kim T.; Weber, Rachel C.; Murphy, Meagan; Ghani, Aisha
Introduction: Divergent thinking is a crucial component of effective problem-solving. This study investigated the divergent thinking of students with visual impairments (i.e., blindness or low vision) in three countries and explored the correlates of their performance on two tasks. Methods: A sample of 52 students with visual impairments completed two divergent thinking tasks, one traditional Alternate Uses task, and one scenario-based task created for this study. Each student's teacher of students with visual impairments completed a questionnaire containing demographic, curriculum, and student characteristics. Results: Of the correlates examined, teacher-rated academic independence, working on grade level, number of expanded core curriculum (ECC) areas of instruction currently received, and ongoing receipt of assistive technology instruction were significantly related to task performance. Discussion: Findings demonstrate the strong relationship between real-life problem-solving, divergent thinking, and academic functioning in students with visual impairments. Further investigation is needed about the relationship between aspects of problem-solving instruction and student outcomes as they relate to divergent thinking. Implications for practitioners: Given the connection of divergent thinking to overall problem-solving ability, teachers should assess these skills in students. Using similar scenario-based real-life tasks, they can also incorporate practice opportunities for divergent thinking within ECC instruction.